2016
DOI: 10.3803/enm.2016.31.4.592
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery of Hypothalamic-Pituitary-Adrenal Axis Is Rapid in Subclinical Cushing Syndrome

Abstract: BackgroundIn subclinical Cushing syndrome (SC), it is assumed that glucocorticoid production is insufficient to cause a clinically recognizable syndrome. Differences in hormonal levels or recovery time of the hypothalamic-pituitary-adrenocortical (HPA) axis after adrenalectomy between patients with overt Cushing syndrome (OC) and SC remain unknown.MethodsThirty-six patients (10 with OC and 26 with SC) with adrenal Cushing syndrome who underwent adrenalectomy from 2004 to 2014 were reviewed retrospectively. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…It was remarkable that at three months after surgery, when the stressful condition was still not present, 35 morning plasma cortisol was > 5 mg/dL in all patients, regardless of the preoperative cortisol degree, and such a level implies the recovery of the HPA axis. 28,37 The present results confirm that there is no clear correlation between recovery time and preoperative cortisol levels. 32 Since a residual adrenal tissue of approximately 10% to 15% offers intact stress capacity 38 and the morphology of the contralateral adrenal glands in the present study were normal, it is reasonable to presume that the volume of residual adrenal tissue, rather than the degree of cortisol secretion, played a crucial role in the time to restoration of eucortisolism, although this finding is limited by the sample size and lack of control of the study.…”
Section: Discussionsupporting
confidence: 77%
“…It was remarkable that at three months after surgery, when the stressful condition was still not present, 35 morning plasma cortisol was > 5 mg/dL in all patients, regardless of the preoperative cortisol degree, and such a level implies the recovery of the HPA axis. 28,37 The present results confirm that there is no clear correlation between recovery time and preoperative cortisol levels. 32 Since a residual adrenal tissue of approximately 10% to 15% offers intact stress capacity 38 and the morphology of the contralateral adrenal glands in the present study were normal, it is reasonable to presume that the volume of residual adrenal tissue, rather than the degree of cortisol secretion, played a crucial role in the time to restoration of eucortisolism, although this finding is limited by the sample size and lack of control of the study.…”
Section: Discussionsupporting
confidence: 77%
“…In this present study, we focused on only SCS patients. Some studies stated that prolonged adrenal insufficiency is more frequent in CS patients than in SCS patients . As CS is symptomatic, the duration of potential morbidity might be shorter than SCS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies stated that prolonged adrenal insufficiency is more frequent in CS patients than in SCS patients. [20][21][22] As CS is symptomatic, the duration of potential morbidity might be shorter than SCS. In addition, the recovery of the HPA axis might depend on the activity of the tumor itself.…”
Section: Discussionmentioning
confidence: 99%
“…The mean recovery time was 6.5 months (range 1–50) in MACE and 11.2 months (range 1–60) in overt CS with a tight relationship between the degree of hypercortisolism and the time to recovery 3 . Kim et al 22 also reported that the recovery time was significantly shorter in patients with MACE than those with overt adrenal CS (4.0 months vs. 17.0 months).…”
Section: Predictors Of Hpa Axis Recoverymentioning
confidence: 96%